Efforts by the Turjawali Traffic Unit to Prevent Traffic Accidents in Purwakarta - Muhammad Arif Rahman (Tanggon Kosala, 2021)
In daily routines, the community carries out activities that require them to move to another place in order to carry out their obligation to use motorized vehicles. This research is based on the background because the traffic accidents in Purwakarta continue to occur despite the efforts of the Turjawali Unit of the Purwakarta Police Traffic Unit to prevent traffic accidents. With the prevention efforts by guarding the accident-prone points, but this has not yet shown the expected results, namely the reduction in accident rates and the creation of kamseltibcarlantas. Therefore, a study was conducted to find out the general picture of accidents that occurred in Purwakarta the efforts made by the Turjawali Unit of the Purwakarta Police Traffic Unit in preventing accidents traffic. This study, using qualitative approach to interview, observation and document review data collection techniques. The research method uses the concept of effort and traffic carried out by the Turjawali Unit of the Purwakarta Police Traffic Unit. Analyzing using performance theory also found that the obstacle was in human resources, namely the ability of the Turjawali Unit because it had not yet implemented specialization development education. The author’s research result suggest the need to improve the quality of the members of the Turjawali Unit by including the members of the Turjawali Unit to carry out specializaed development education in accordance with their dutie, afterwards forming an accident prevention task force by involving side agencies such as the trans portation agency and the public spatial planning service not to forget involving the community which is considered to be potential in efforts to prevent accidents in Purwakarta so that hopes for a reduction in accident rates and the creation of kamseltibcarlantas in Purwakarta can be achieved.